Two new species of Manahunca, redescription of its type species, current conservation status of the genus and a survey of male glands in Stenostygninae (Opiliones: Laniatores: Biantidae) - Alegre, Aylin; Gainett, Guilherme; Iborra, Germán López; Giribet, Gonzalo (Zootaxa, 2019)
Manahunca bielawskii Šilhavý, 1973, the type species of the genus Manahunca Šilhavý, 1973, is redescribed based on abundant material from the type locality, including new data on its morphological variability and penis morphology. A neotype for M. bielawskii is herein designated due to the unknown whereabouts of the original holotype. Manahunca silhavyi Avram, 1977, is regarded as a new junior subjective synonym of M. bielawskii. In addition, two new species of Manahunca are described, M. turquino Alegre, Gainett & Giribet, n. sp. and M. matazon Alegre, Gainett & Giribet, n. sp. based on additional specimens from eastern Cuba, for which we provide new data on their geographical distribution, intraspecific variability and habitat. A new diagnosis and emended geographic distribution of the known species of Manahunca are provided, with hints on the current conservation status. The sexually dimorphic glandular structures found on the metatarsus III of males are explored for taxonomic significance in ten species of Stenostygninae. The existence of male dimorphism, most evident in the robustness of the chelicerae, is reported for two of the studied Manahunca species.